Effectiveness of Animated Video Assisted Experiential Learning in Improving Elementary Students Learning Outcomes - Regina Elriana Oki Prigiya; Bayu Purwo Adhi; Eko Pujianto (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2026)
This study examines the effectiveness of the Experiential Learning model assisted by animated videos in improving the learning outcomes of Natural and Social Sciences (IPAS) students at the elementary school level. A quasi-experiment with a Non-Equivalent Control Group Design was used, with purposive sampling selecting students from Presidential Elementary School, Beriwit State Elementary School 1, and Beriwit State Elementary School 2. The experimental group received animated video-assisted learning, while the control group followed conventional methods. Validity and reliability tests were conducted, and data were analyzed using an independent sample t-test. Results showed the experimental class had a significantly higher post-test average score (83.77) compared to the control group (65.00). The hypothesis test yielded a t-value of 2.018, greater than the t-table value of 1.771, with a significance of 0.007 (< 0.05). These findings confirm that the Experiential Learning model with animated videos effectively enhances students' learning outcomes. This model promotes active engagement and can be widely applied in elementary school curricula.